KOMUNIKASI PEMASARAN GIGIGO DENTAL CARE MELALUI MEDIA SOSIAL INSTAGRAM - Ollen Kumala Murwa; Muadz Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The background of this research is the low public awareness regarding dental health. Many people still consider dental treatment expensive and frightening, making it less of a priority. On the other hand, the rise of social media, especially Instagram, provides a great opportunity to reach a wide audience. Gigigo Dental Care, a rapidly growing dental clinic, leverages Instagram to build its brand image, deliver educational content, and promote services creatively.This study aims to analyze Gigigo Dental Care's marketing communication through Instagram using a qualitative case study approach. Data were collected through in-depth interviews with the CEO, marketing team, and customers, as well as documentation of content from @gigigo.id. The analysis employed the 7P marketing mix framework (Product, Price, Place, Promotion, People, Process, Physical Evidence).The findings reveal that Instagram is consistently used to share service information, promotions, education, and customer engagement. Creative visual content such as reels, feed posts, stories, and live sessions are the main attraction for young audiences. With competitive pricing, seasonal promotions, doctor involvement in educational content, and a professional visual identity, Gigigo successfully attracts many new patients. This research highlights the importance of social media-based marketing communication to increase consumer awareness and trust in healthcare services. Keywords: marketing communication, Instagram, dental health, marketing mix, social media